The macroeconomic effects of the EU recovery and resilience facility: A premliminary assessment - Sebastian Watzka; Andrew Watt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
This policy brief analyses the macroeconomic effects of the EU's Recovery and Resilience Facility (RRF). We present the basics of the RRF and then use the macroeconometric multi-country model NiGEM to analyse the facility's macroeconomic effects. The simulations show, first, that if the funds are in fact used to finance additional public investment (as intended), public capital stocks throughout the EU will increase markedly during the time of the RRF. Second, in some especially hard-hit southern European countries, the RRF would offset a significant share of the output lost during the pandemic. Third, as gains in GDP due to the RRF will be much stronger in (poorer) southern and eastern European countries, the RRF has the potential to reduce economic divergence. Finally, and in direct consequence of the increased GDP, the RRF will lead to lower public debt ratios; between 2.0 and 4.4 percentage points below baseline for southern European countries in 2023.
Keywords: 330